The curious incident of the dog in the night-time / Simon Stephens ; adapted from the novel by Mark Haddon. - Stephens, Simon, 1971- (Methuen Drama, 2012)
Christopher, stands beside Mrs Shears's dead dog. It has been speared with a garden fork, it is seven minutes after midnight, and Christopher is under suspicion. He records each fact in the book he is writing to solve the mystery of who murdered Wellington.